THE EFFECT OF ACCOUNTING CONSERVATISM ON CASH HOLDINGS WITH CONTROLLING SHAREHOLDERS AS MODERATING VARIABLE - Shakirani, Maritza Aulia; Ghozali, Imam (Diponegoro Journal of Accounting, 2021)
According to prior studies, accounting conservatism defined as an accounting practice principle that recognize losses in a more timely manner than recognizing profit. The purpose of this research is to examine the influence of accounting conservatism on cash holdings in a company with the role of controlling shareholders as a moderating variable. There are two forms of accounting conservatism occurred in this research, namely conditional accounting conservatism and unconditional accounting conservatism. The role of controlling shareholders in this research is utilized to discover its influence towards the relationship between both types of accounting conservatism and cash holdings. The analysis method used is the multiple linear regression analysis, and the analysis is conducted using SPSS software. The total sample used is amounting to 46 total of companies from banking sector that are listed in Indonesia Stock Exchange (IDX) with the research period of 2018-2020, and are selected using purposive sampling method.            The findings of this research indicate that conditional accounting conservatism significantly affect the cash holdings. On the other hands, unconditional accounting conservatism does not significantly affect the cash holdings. Furthermore, the role of controlling shareholders does not affect the relationship between both of the two forms of accounting conservatism and cash holdings, this might be due to the level of ownership from the controlling shareholders.